Prevalence of workplace violence against health care workers in hospital and pre-hospital settings: An umbrella review of meta-analyses - Sahebi, Ali; Golitaleb, Mohamad; Moayedi, Siamak; Torres, Mercedes; Sheikhbardsiri, Hojjat (Frontiers in Public Health, 2022)
Introduction: Workplace violence (WPV) is associated with adverse consequences for patients and health care workers (HCWs). The aim of this study was to assess the prevalence of WPV against HCWs in the hospital and pre-hospital settings. Methods: Using PRISMA guidelines, data resources including Scopus, PubMed, Web of Science, and Google Scholar were used for the search. The searches were conducted without any time limit until the end of December 2021. The random-effects model was used for this meta-analysis. I2 index was used to examine heterogeneity and the Egger test was used to examine publication bias. Results: Of the 255 studies identified, 14 studies entered the umbrella review. The overall prevalence was as follows: WPV (58.7%); physical violence (20.8%); verbal violence (66.8%); and sexual harassment (10.5%). Conclusion: The prevalence of WPV and its types against HCWs is relatively high. WPV is associated with physical, psychological, and occupational consequences. Measures should be taken to reduce the consequences of WPV.